Pengaruh Kualitas Pelayanan dan Digital Payment Terhadap Kepuasan Konsumen di Metro Swalayan Kota Malang - Nimas Rahayu Sri Wilujeng; Ayu Sulasari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The rapid growth of the retail industry in Indonesia motivates businesses to innovate, especially in improving service quality and using digital payments. Metro Swalayan Malang City has adopted these two things to increase the customer satisfaction. This study aims to examine the effect of service quality and digital payments on customer satisfaction, both partially and simultaneously. This research used a quantitative approach with an explanatory method. The data were primary and secondary data were used, collected through observation and interviews. The data respondents were collected through online and offline questionnaires using purposive sampling technique from 100 respondents. The data analysis was carried out using IBM SPSS 23 with descriptive methods, classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing. The results showed that service quality and digital payments had a positive and significant effect on customer satisfaction, both partially and simultaneously. The coefficient of determination of 46.5% indicated that these two variables were able to explain most of the variation in customer satisfaction.  In conclusion, improving service quality and ease of digital payment effectively increases customer satisfaction at Metro Supermarket Malang City.